1975
DOI: 10.1530/jrf.0.0430167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gonadotrophin-Releasing Hormone and Human Chorionic Gonadotrophin on the Response of the Ewe to Pregnant Mare Serum Gonadotrophin

Abstract: An experiment was conducted to determine whether gonadotrophin-releasing hormone (Gn-RH)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1983
1983
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…A decrease in the number of ova fertilized and transferable embryos at high doses of exogenous gonadotrophins has also been reported in other reports in both sheep (Moor et al, 1985) and cattle (McGowan et al, 1983;Donaldson and Ward, 1985;Donaldson et al, 1986). It has been demonstrated that high levels of gonadotrophins alter endocrine profiles (Quirke and Hanrahan, 1975;Whyman and Moore, 1980 ;McNatty et al, 1982), biochemical functions of oocytes (Moor et al, 1985) and sperm transport (Armstrong and Evans, 1984). All this may negatively influence the number and quality of fertilized ova.…”
Section: Discussionsupporting
confidence: 55%
“…A decrease in the number of ova fertilized and transferable embryos at high doses of exogenous gonadotrophins has also been reported in other reports in both sheep (Moor et al, 1985) and cattle (McGowan et al, 1983;Donaldson and Ward, 1985;Donaldson et al, 1986). It has been demonstrated that high levels of gonadotrophins alter endocrine profiles (Quirke and Hanrahan, 1975;Whyman and Moore, 1980 ;McNatty et al, 1982), biochemical functions of oocytes (Moor et al, 1985) and sperm transport (Armstrong and Evans, 1984). All this may negatively influence the number and quality of fertilized ova.…”
Section: Discussionsupporting
confidence: 55%
“…It is possible that by giving an ovulating agent such as human chorionic gonadotrophin or luteinizing hormone releasing hormone (Nancarrow et af. 1984;Quirke and Hanrahan 1975) advantage may be taken of the increased ovarian response that was exhibited by some groups of ewes, particularly group A after treatment with 1500 i.u. PMSG.…”
Section: Discussioumentioning
confidence: 99%